2016
DOI: 10.1177/2333392816673290
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Cancer Symptoms and Barriers to Seeking Medical Help Among Adult People Attending Primary Care Settings in Oman

Abstract: Objectives:To explore the public’s awareness of cancer symptoms and the barriers to seeking medical help among Omani adults attending primary care settings in Muscat governorate, the capital city of Oman.Methods:The Cancer Awareness Measure (CAM) questionnaire (translated into Arabic) was used to collect data from a total of 12 randomly selected local health centers (LHCs) in Muscat governorate, the capital city of Oman. Omani adults aged 18 years and above attending LHCs during the study period were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 33 publications
7
24
0
Order By: Relevance
“…A similar study from the UK which used the CAM questionnaire showed that awareness levels among adolescents of cancer symptoms was also low, a similar finding to the current study (Kyle et al, 2013). Previous studies conducted in Oman among adults indicated low awareness levels in identifying risk factors and symptoms for the most common cancers, and the levels were also low for specific types of cancer, such as colorectal and ovarian (Al-Azri et al, 2015;Al-Azri et al, 2016;Al-Azri et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…A similar study from the UK which used the CAM questionnaire showed that awareness levels among adolescents of cancer symptoms was also low, a similar finding to the current study (Kyle et al, 2013). Previous studies conducted in Oman among adults indicated low awareness levels in identifying risk factors and symptoms for the most common cancers, and the levels were also low for specific types of cancer, such as colorectal and ovarian (Al-Azri et al, 2015;Al-Azri et al, 2016;Al-Azri et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Female adolescents in this study were more likely than the males to identify several emotional barriers from seeking medical help, such as "embarrassment", "being scared" and "worried about what the doctor might find". There is a paucity in the literature regarding teenage cancer diagnosis delay; one study from the UK found that the reasons for delay were mainly attributable to the actions of healthcare professionals (Fern et al, 2011) Previous studies conducted in Oman and in the UK showed that women were more likely than men to perceive similar emotional barriers to the ones listed above which would prevent them from seeking early medical help (Al-Azri et al, 2016;Robb et al, 2009). Women have been noted to worry about cancer symptoms, due to being worried about side effects of treatments or because they believed that there was no cure for cancer, which could lead to a delay in their diagnosis (Murphy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations